Comparative analysis of oral microbiome in saliva samples of oral leukoplakia, proliferative leukoplakia and oral squamous cell carcinoma - Rossella Intini; Sol Balsells; Leticia Bagan; Giulio Fortuna; Herve Sroussi; Jose Bagan; Jose Bagan (Frontiers in Oral Health)
BackgroundOral potentially malignant disorders (OPMDs), including conventional leukoplakia (OL) and proliferative verrucous leukoplakia (PVL), have distinct risks of progression to oral squamous cell carcinoma (OSCC). A role of the oral microbiome in this transformation is increasingly recognized, but its contribution remains unclear.ObjectiveThis study aimed to analyze and compare the oral microbiota in patients with OL, PVL, and OSCC using 16S rRNA gene sequencing of saliva samples to identify microbial signatures associated with disease progression and to uncover potential biomarkers that would justify an aggressive treatment of OPMDs.MethodsSixty-six subjects with OPMDs were enrolled, comprising OL (n = 10), PVL (n = 28), and OSCC (n = 28). Saliva samples were collected, and DNA was extracted. The V3–V4 regions of the 16S rRNA gene were sequenced using the Illumina MiSeq platform. Bioinformatic analyses, including diversity assessments and taxonomic classification with the SILVA v138 database, were performed using QIIME2. Alpha diversity was evaluated with Chao1, Shannon, and Simpson indices, while beta diversity was assessed using Bray-Curtis and Jaccard distances.ResultsPVL exhibited the highest species richness, followed by OL, with OSCC showing the lowest diversity. While alpha diversity differences among the groups were not statistically significant (p > 0.05), beta diversity revealed distinct microbial community structures between OL and both PVL and OSCC (p < 0.05), but not between PVL and OSCC. At the phylum level, Firmicutes predominated across all groups, with significantly higher Actinobacteriota levels in OL (p = 0.002).ConclusionDistinct microbial patterns differentiate OL from PVL and OSCC, with OL being different from PVL and OSCC, suggesting progressive microbial dysbiosis in malignant transformation. These findings support the potential of oral microbiome profiling as a non-invasive diagnostic and prognostic tool in oral oncology and highlight the need for longitudinal studies to establish causal relationships.